2016
DOI: 10.1080/09712119.2016.1190735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different raising systems on growth performance, carcass, and meat quality of medium-growing chickens

Abstract: A growing awareness of human health, nutrition, and animal welfare concerns has led to the development of specialty markets for organic food. Poultry produced in alternative systems, such as free-range or organic, are part of this trend. The aim of the present study was to evaluate the differences in growth performance, carcass traits, and meat quality of medium-growing chickens raised in three different raising systems: indoor-floor, cage, and free-range. One hundred and twenty female Lingnanhuang medium-grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 18 publications
10
19
1
Order By: Relevance
“…Meat drip loss and shear force are important parameters that can directly affect the tenderness and juiciness of meat, with meat that has a higher drip loss value considered to be drier or tougher. In the current study, the pectoralis major and thigh muscles of birds raised under FRS conditions had lower drip loss and higher shear force than those of chickens reared under CRS conditions, which was consistent with the findings of previous studies (Li et al., ; Yang et al., ). Under FRS conditions, the greater amount of physical activity may enhance the development and density of muscle fibers in chickens, and this might be a major factor underlying the increased shear force and decreased drip loss (Vestergaard et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Meat drip loss and shear force are important parameters that can directly affect the tenderness and juiciness of meat, with meat that has a higher drip loss value considered to be drier or tougher. In the current study, the pectoralis major and thigh muscles of birds raised under FRS conditions had lower drip loss and higher shear force than those of chickens reared under CRS conditions, which was consistent with the findings of previous studies (Li et al., ; Yang et al., ). Under FRS conditions, the greater amount of physical activity may enhance the development and density of muscle fibers in chickens, and this might be a major factor underlying the increased shear force and decreased drip loss (Vestergaard et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…It was demonstrated that the percentage of breast muscle in a free‐range group at 35 weeks of age was higher than that of birds in a cage group (Fu et al., ). Consistent with a previous study (Li, Luo, Wang, & Guo, ), we found that birds reared in the FRS had higher breast yield than those in the CRS. In contrast, it was reported that different rearing systems had no significant effects on the carcass traits of chickens (Chen, Jiang et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, Cömert et al (2016) observed significantly higher live weight in fast-growing chickens, reared outdoors, but no effect of the rearing system in slow-growing lines. Our results are in line with Wang et al (2009) who reported lower live weight in slow-growing chickens reared free-range with access to grass paddocks and Li et al (2017) in medium -growing chickens raised indoors on floor and outdoors with pasture. However, both studies did not observe any significant difference between the free-range and conventional system in regard to the dressing percentage.…”
Section: Carcass Traitssupporting
confidence: 92%